PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP HASIL BELAJAR SISWA - Irene Vania Lumbantobing (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
This study aims to determine whether there is an influence of the NHT cooperative learning model on student learning outcomes at SMAN 10 Medan. This type of research is a quasi-experimental study with two groups pre-test and post-test research designs. The research sample was random sampling technique. The data of this study were collected using learning outcomes test instruments. The test is a multiple choice of 20 questions. From the data analysis for the experimental class, pre-tests (53,194 ± 10.43) and post-tests were obtained (81.53 ± 17,395). In the control class, pre-tests (50.94 ± 10.91) and tests (67,027 ± 9,38) were obtained. The results of testing the hypothesis by using the one-party t-test at = 0.05 and dk = 78 obtained tcount> t table or (3.453)> (1.6687) then Ha is accepted, increasing student learning outcomes after being given the treatment of cooperative learning type nht (numbered heads together) better than conventional learning in thermochemical material at SMAN 10 Medan